How large is the mitigation potential of natural climate solutions in China?. (1st January 2023) - Wang, Daju; Li, Yuanqiao; Xia, Jiangzhou; Liu, Changxin; Chen, Han; Teng, Fei; He, Bin; Shi, Weiyu; Qin, Zhangcai; Yuan, Wenping
Abstract: China is facing a huge challenge in achieving its carbon neutrality goal by 2060 given that it is currently one of the world's largest greenhouse gas (GHG) emitters and has set a very short timeline for going from peak emissions to carbon neutrality. Natural climate solutions (NCS) that protect, manage, and restore ecosystems have shown substantial potential for increasing carbon sinks or reducing GHG emissions to offset fossil fuel CO2 emissions. This study quantified the mitigation potential of 18 NCS pathways in China at 0.67–1.65 Gigatonne of CO2 equivalent (Gt CO2 e) yr −1 averaged from 2020 to 2060, which is even larger than the size of the current national terrestrial carbon sink. Compared with a previous global estimate, our results show a lower mitigation potential in forest ecosystems but a much greater potential for cropland ecosystems in China. From 2020 to 2060, all 18 pathways combined can provide cost-effective mitigation compared to the global social cost of CO2 emission and carbon prices, and 98.6% and 83.3% mitigation potential are cost-effective, respectively. This study further showed that immediate action provides the greatest mitigation. Our estimates highlight the important role of NCS in achieving the national carbon neutrality goal because of their large mitigation potential and cost-effectiveness.